2014
DOI: 10.1615/critrevoncog.2014012044
|View full text |Cite
|
Sign up to set email alerts
|

Role of Raf Kinase Inhibitor Protein in Helicobacter pylori-Mediated Signaling in Gastric Cancer

Abstract: Helicobacter pylori is a helical bacterium that colonizes the stomach in over half of the world’s population. Infection with this bacterium has been linked to peptic ulcer disease and gastric cancer. The bacterium has been shown to affect regulatory pathways in its host cells through specific virulence factors that control gene expression. Infection with H. pylori increases levels of phosphorylation of Raf kinase inhibitor protein (pRKIP) in gastric adenocarcinoma (AGS) cells in vitro and in vivo. We investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…We do not know the reason why peptic ulcer is negatively associated with TSC. Increased expression of phosphorylated Raf kinase inhibitor protein by gastric cells infected with H. pylori is abrogated by rapamycin, an mTOR inhibitor. Thus, mTOR might modulate the signalling pathways in gastric cells infected with H. pylori , contributing to the pathogenesis of peptic ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…We do not know the reason why peptic ulcer is negatively associated with TSC. Increased expression of phosphorylated Raf kinase inhibitor protein by gastric cells infected with H. pylori is abrogated by rapamycin, an mTOR inhibitor. Thus, mTOR might modulate the signalling pathways in gastric cells infected with H. pylori , contributing to the pathogenesis of peptic ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…At a post-translational level, a phosphorylation of RKIP at Serine 153 (pSer153-RKIP) by protein kinase C ζ (PKCζ) has been found in several cancer types to account for loss of RKIP activity as a Raf-1 proto-oncogene, serine/threonine kinase/mitogen-activated protein kinase kinase/extracellular signal-regulated kinase (Raf/MEK/ERK) and GPCR inhibitor, through inhibition of G protein-coupled receptor kinase 2(GRK2) [6,30,74,75,76,77,78]. In some cancers, the nuclear pSer153-RKIP levels significantly correlated with poor response to therapy and overall prognosis [75,79].…”
Section: Rkip Regulationmentioning
confidence: 99%
“…Contrarily, the inhibition of Raf-mediated STAT3 serine phosphorylation is attained through RKIP-induced suppression of Raf-1 activity [97]. Accordingly, RKIP expression has been found to be inversely correlated with phosphorylated STAT3 (pSTAT3) levels in different tumor types [75,76,98,99,100]. …”
Section: Central Signaling Pathways Regulated By Rkipmentioning
confidence: 99%
“…Furthermore, Du et al suggested that cholesterol glucosylation by H. pylori modulates the lipid-raft trafficking endocytic pathway that requires PI3K activation, thereby favoring prolonged bacterial survival inside macrophages. Finally, Nisimova et al investigated the role of H. pylori infection in the phosphorylation of pro-apoptotic factor Raf kinase inhibitor protein (RKIP) [48]. They concluded that H. pylori in vitro and in vivo infection can induce phosphorylation and subsequent activation of RKIP which in turn can downregulate protumorigenic factors such as EGFR, Raf-1, and MAPKs and therefore effectively attenuating pro-survival signals in gastric tumorigenesis.…”
Section: Other Bacterial Virulence Factorsmentioning
confidence: 99%